SAPU-SAPU FISH (Hyposarcus pardalis) AS A SINGLE PROTEIN SOURCE FOR LAYING MOJOSARI DUCKS - Indarsih, B.; Asnawi, A.; Purnamasari, D. K. (Diponegoro University, 2016)
The present study was conducted to evaluate the optimum level of dietary inclusion and the form of feeding sapu-sapu fish (SSF) as a single protein source for feed components of small holder Mojosari duck farming. A total of 180 twenty four wk-old laying ducks were fed with two forms (sun-dried and ground-fresh) and three levels of SSF (10, 20 and 30%) from 24 to 32 wk of age. Experimental diets were formulated containing 105.1; 141.5 and 177.9 g/kg crude protein and 3078; 3065 and 3052 kcal metabolizable energy (ME) /kg diet. Production performance and egg quality were measured. The form of SSF had a significant effect (P<0.0001) on feed intake, egg production, feed conversion, egg mass and egg number except final body weight. No significant effects (P>0.05) were found on all of the performance parameters measured due to feeding levels of SSF except feed intake and final body weight. The interaction of form and feeding level was significant (P<0.05) on egg and body weights. Low performance and egg quality were observed in the birds fed a diet containing the dried SSF. It can be suggested that local ducks required 20% SSF as a single protein source for maximum egg production (41.2%) and total egg number per wk (3.1 eggs/bird/wk) during 8 wk of rearing period. Egg quality can be improved by feeding the fresh SSF. However, due to be sufficiently better processing technique, the dried SSF would be potential to replace the common fish for laying ducks.